2019
DOI: 10.1177/0907568219828428
|View full text |Cite
|
Sign up to set email alerts
|

Children’s active participation during meals in Early Childhood and Care Institutions

Abstract: The meal in Early Childhood and Care Institutions is often characterized by routines and rules determined by adults. This, if correct, is not in line with today’s ideals about children’s involvement and active participation. In this article I argue for children’s active participation, which is a key prerequisite in the understanding of seeing meals as a democratic arena. Next, I review the theoretical work on how Early Childhood and Care Institutions staff can arrange for meals to be characterized by children’… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Not all the educators' practices, however, manifested a cultural reformulation of this kind; instead, some of them reproduced institutional order. This was most evident during the routines pertaining to night sleep or mealtimes which, in line with the ideas presented by Glaser (2019), tended to trigger a more adult-directed approach to ECEC.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Not all the educators' practices, however, manifested a cultural reformulation of this kind; instead, some of them reproduced institutional order. This was most evident during the routines pertaining to night sleep or mealtimes which, in line with the ideas presented by Glaser (2019), tended to trigger a more adult-directed approach to ECEC.…”
Section: Discussionmentioning
confidence: 55%
“…In line with the United Nations Convention on the Rights of the Child (1989), the National Curriculum Guidelines on ECEC in Finland (Finnish National Board for Education, 2018) highlight the importance of listening to and taking into consideration children's initiatives and thereby contributing to their belonging. These aims challenge the traditional institutional culture, which is informed by rather fixed practices and hierarchical positions between children and educators (Glaser, 2019). Although common to all forms of ECEC, the aim of children's belonging is most likely to be realized in evening ECEC where it is underpinned by both the cultural assumptions concerning evening time and its unique social environment.…”
Section: A Child's Belonging In Ececmentioning
confidence: 99%
“…Finally, studies on ECE teachers' beliefs about the strategies adopted to enhance children's participation have shown that these techniques include asking children questions, involving children in role play, listening to the child without criticism [12], recognising children's meaning-making abilities during participatory practices [31], displaying a positive response to children's ideas [12,13,18,32], encouraging and actively creating opportunities for dialogue and decision-making, and involving children in the co-design of activities and processes [13,15,16,18,20,23,31,32].…”
Section: The Content Of Beliefs About Children's Participation In Ecementioning
confidence: 99%
“…In terms of children's lived citizenship, several studies (e.g., Glaser, 2019;Salmon et al, 2018;Sierra-Cedillo et al, 2019) have examined intergenerational relationships in early childhood settings and indicated that adults (e.g., children's parents, kindergarten teachers) critically influence young children's citizenship, especially their practice as citizens. For example, the involvement of parents can facilitate a stronger connection between early childhood settings and families, encouraging children to develop their sense of identity and belonging (Salmon et al, 2018).…”
Section: Children's Lived Citizenship In Early Childhood Settingsmentioning
confidence: 99%
“…Recognising children's negotiated position as citizens could shed new light on the current effort of respecting or empowering young children in early childhood settings. A number of previous studies focus on the value of citizenship in early childhood education, and encourage children's participation from the adults' side (e.g., Glaser, 2019;Sierra-Cedillo et al, 2019). However, this is far not enough to see the dynamic power network and children's subjectivities in early childhood settings.…”
Section: Power Dynamics and Negotiated Citizenship In Early Childhood...mentioning
confidence: 99%